(untitled) (Swiss Medical Weekly, 2011)
QUESTIONS UNDER STUDY: Prevalence of symptoms, with a focus on fatigue, and changes of symptoms were explored over three months in outpatients with lymphoma, lung, breast or colorectal cancer, receiving chemotherapy in the oncology outpatient clinic of a Swiss tertiary care hospital. METHODS: Prospective, descriptive design; symptom prevalence was measured at start of chemotherapy (T1), and one week prior to the third and fourth cycle (T2, T3). Included were patients starting chemotherapy, with expected survival of >3 months, irrespective of stage of disease. The Memorial Symptom Assessment Scale was used to assess 32 symptoms; fatigue was measured with the FACIT-Fatigue Scale (negative scale). Data were analysed using descriptive statistics and random-intercept regression models. RESULTS: 77 patients participated at T1, 58 and 50 at T2 and T3. Patients experienced on average 9.8, 14.4, and 13.7 symptoms, showing a significant increase over time. Lack of energy and feeling drowsy were most frequent. Symptom scores for lack of energy, changes in skin, pain, and feeling drowsy remained >2 over time (scale 0–4, higher scores = more symptoms). Fatigue mean scores were 36.3, 30.2, and 31.3, showing a significant increase of fatigue over time. Individual symptom trajectories varied widely within and among patients. CONCLUSIONS: High symptom prevalence at start of chemotherapy as well as over time and great variability in symptom experience call for an individual, systematic symptom assessment and management that does not focus solely on side-effects of therapy but includes disease-related symptoms to achieve satisfactory control of symptoms in outpatients receiving chemotherapy.